SUITABILITY OF RESIDENTIAL LAND USE WITH REGIONAL SPATIAL PLANNING ON THE COAST OF WANGI-WANGI ISLAND, WAKATOBI REGENCY - Padar, Sekar Alim; Barkey, Roland Alexander; Zubair, Hazairin; Setiawan, Alim; Ode, Muhamad Fadli (USN Kolaka, 2024)
The Bajo Mola Raya settlement on Wangi-wangi Island, Wakatobi Regency, is experiencing development that does not align with spatial planning aspects. This research aims to analyze the development of existing residential land use in the Mola Raya area in accordance with the Regional Spatial Plan (RTRW) of Wakatobi Regency; to identify the factors causing the development of residential land use in the Mola Raya area in accordance with the Regional Spatial Plan (RTRW) of Wakatobi Regency, which consists of external and internal factors. External factors include: (a) population growth; (b) community economy; and (c) community socio-culture, while internal factors consist of (d) supervision; (e) licensing; and (f) enforcement. The method used is the map overlay technique. This analysis begins with the results of on-screen digitization of Google Earth imagery from 2018. Then, an overlay technique was performed with the spatial planning map of the Wangi-Wangi Island residential area and a descriptive presentation of the results from the FFA analysis, interviews, and FGDs. The results of this study indicate that the development of residential areas not in accordance with the RTRWK is found in Mola Utara Village with a conformity of 76.53% and Mola Nelayan Bakti Village with 76.87% conformity to the spatial planning of the Wangi-Wangi Island residential area. Furthermore, the factors most influencing the development of the Bajo Mola Raya settlement were found to be the increase in population, the economy of the community, and the socio-cultural aspects of the society. The internal factors indicate a lack of supervision, licensing, and enforcement from the local government.